Radio drama : theory and practice - Crook, Tim, 1959- (Routledge, 1999)
"Radio Drama brings together the practical skills needed for radio drama, such as directing, writing and sound design, with media history and communication theory. From the early audio broadcasts of 1914 and the development of General Electric's New York WGY station in 1922, through Orson Welles's startling Hallowe'en broadcast of War of the Worlds in 1938, to more recent radio spoofs and the subversive challenge from 'media guerrillas', Tim Crook explores the history and contemporary practice of radio drama. Challenging the belief that sound drama is a 'blind medium', Radio Drama shows how experimentation in radio narrative has blurred the dividing line between fiction and reality in modern media.